Value for Money Moderates External Pressure, Environmental Uncertainty on Budget Goals Clarity - Tumpal Manik (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2020)
The research purpose is to analyze effect of external pressures, environmental uncertainty, budget quality, locus of control and value for money on budget goals clarity, then to test value for money and locus of control to moderate the relationship between external pressure, environmental uncertainty, quality budget against clarity on budget goals clarity. The research was conducted in Kepulauan Riau Province, used 85 data questionnaires getting from despondences. the first Data processing used classical assumption test, validity and reliability test, and then testing hypothesis test of used t-test and f-test. Empirically, the first to investigate the statistical results of research hypothesis shown that external pressure is a significant positive effect on budget goals clarity; second, environmental uncertainty is a positive significant effect on budget goals clarity; fourth, the budget quality is a significant positive effect budget goals clarity; third, value for money is a positive significant effect on budget goals clarity; fourth, Then the results of the moderation test show that the value for many can weaken the relationship between external pressure and environmental uncertainty on budget goals clarity, but value for many can be to improve relationship between budget quality on budget goals clarity. The final Empirical test to shown that locus of control is not moderating variable between external pressure, environmental uncertainty on budget goals clarity.